STRENGTHS-BASED APPROACH AND ITS EFFECT ON ATTENDANCE, ACADEMIC ACHIEVEMENT AND EFL MOTIVATION - Yılmaz, Emrullah; Akpinar, Burhan (My University, 2020)
The purpose of this study is to examine the effect of Strengths Based Approach (SBA) on attendance, academic achievement and student motivation in English class. For this purpose, an experimental study was carried out with freshman students at a state university in Turkey in the spring term of 2011-2012 academic year. The sampling of the study consisted of 66 students in total, 33 students in experimental group and 33 students in control group. Pretest posttest quasi-experimental design with a control group was used in the study. Clifton StrengthsfinderTM was used to determine the talent themes of students. The data on the motivation levels of students were obtained through the motivation scale, which was adapted from Attitude/Motivation Test Battery developed by Gardner (1985). The data regarding the attendance percentages of students in English class were obtained from attendance sheets taken by the researcher weekly. Students’ exam scores in mid-term and final exams administered by the researcher in both terms were taken into consideration for the academic achievement of students. The study indicated that the most frequently encountered talent themes were restorative (f=16), responsibility (f=11), deliberative (f=9), ideation (f=9) and learner (f=9) respectively. Also, SBA affected the attendance rates of students positively in favour of experimental group; however, it didn’t have a significant effect on students’ academic achievement and motivation levels. It is considered important to study SBA, which is a fairly new area of study for both the world and Turkey.
Keywords: Eğitim; Eğitim Araştırmaları